2022
DOI: 10.1002/anie.202208746
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Reagents for Enzyme‐Catalyzed Methylation

Abstract: Late-stage methylation is a key technology in the development of pharmaceutical compounds. Methyltransferase biocatalysis may provide powerful options to insert methyl groups into complex molecules with high regio-and chemoselectivity. The challenge of a large-scale application of methyltransferases is their dependence on S-adenosylmethionine (SAM) as a stoichiometric, and thus exceedingly expensive co-substrate. As a solution to this problem, we and others have explored the use of methyl halides as reagents f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 52 publications
2
51
0
3
Order By: Relevance
“…[37] These conclusions on the role of the disordered N-terminus in more efficient binding of bulkier substrates is in agreement with results from the Seebeck group obtained through X-ray crystallography. [14] Having selective enzymes and simple reagents in hand, we finally aimed to understand the scope and limitation of this approach in preparative scale reactions. We synthesized the methylated benzimidazoles 2 f and 2 g using either MeI…”
Section: Methodsmentioning
confidence: 99%
“…[37] These conclusions on the role of the disordered N-terminus in more efficient binding of bulkier substrates is in agreement with results from the Seebeck group obtained through X-ray crystallography. [14] Having selective enzymes and simple reagents in hand, we finally aimed to understand the scope and limitation of this approach in preparative scale reactions. We synthesized the methylated benzimidazoles 2 f and 2 g using either MeI…”
Section: Methodsmentioning
confidence: 99%
“…[12] The cascade is driven by a promiscuous anion MT that uses iodo-and bromoalkanes as well as methylsulfates and -sulfonates as simple precursors to generate SAM or analogs thereof through enzymatic alkylation of S-adenosyl-Lhomocysteine. [9,11,13,14] A second MT utilizes SAM (or its analogue) as electrophile in highly selective methylation/ alkylation reactions. In a first study, we reported that this biocatalytic system can be engineered to methylate pyrazoles with high regioselectivity using iodomethane as reagent.…”
mentioning
confidence: 99%
“…[9,11] Very recently the Seebeck group has also reported that methylsulfates and -sulfonates can be used as methyl source. [14] Since anion MTs and related enzymes do not only bind halides, [37] but also hydrogen sulfide anion, [38,39] thiocyanate [37,40] and phosphonates, [41] we postulated that such enzymes could also activate a broader range of leaving groups for SAH methylation (and SAM regeneration). We studied the promiscuous activity of our in-house anion MT library to activate phosphates, mesylates and tosylates as leaving groups (Figure S14).…”
mentioning
confidence: 99%
See 2 more Smart Citations